Peran promosi kesehatan terhadap tingkat motivasi pasien mendapatkan pelayanan fisioterapi di wilayah kerja Puskesmas Bantimurung Kecamatan Bantimurung Kabupaten Maros - Nur Fa'izah; Utami Sasmita Lestari (Berita Kedokteran Masyarakat (BKM), 2017)
The role of health promotion and the level of patient motivation getting physiotherapy services in public health center of BantimurungPurposeThe purpose of this study was to evaluate the result of media meeting coverage on breastfeeding promotion in mass media. MethodsThis study used a pre-experimental quantitative research with one group pre-test and post-test design. The population samples of this research were all patients who are in the working area of Puskesmas Bantimurung, Bantimurung district of Maros during the years 2013-2014 totaling 46 people, and all patients were respondents in the study. ResultsThe results of data processing show the increase of patient motivation to get physiotherapy services in the working area of Puskesmas Bantimurung. Results show the motivation increased 20.06%. ConclusionThis finding suggests that health promotion is proven to increase patient motivation in the work area of Puskesmas Bantimurung. It is expected that patients will continue to maintain an active role in the search for physiotherapy services in accordance with the conditions and also remain always active in seeking information about their disease.